2013
DOI: 10.1200/jco.2012.47.7430
|View full text |Cite
|
Sign up to set email alerts
|

Functional Decline in Older Patients With Cancer Receiving First-Line Chemotherapy

Abstract: Our results outline associations between baseline depression, instrumental dependencies, and early functional decline during chemotherapy for older patients. ADL should be sequentially evaluated early during treatment. Baseline evaluation of GDS15 and IADL may be proposed to anticipate this event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
173
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(198 citation statements)
references
References 41 publications
(13 reference statements)
10
173
3
1
Order By: Relevance
“…Finally, 16 publications from 15 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], involving 4187 patients, were included in the analysis. Crossreferencing yielded no additional results.…”
Section: Search Outcomementioning
confidence: 99%
“…Finally, 16 publications from 15 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], involving 4187 patients, were included in the analysis. Crossreferencing yielded no additional results.…”
Section: Search Outcomementioning
confidence: 99%
“…self-reported 15-item measure, is also predictive of an increased risk of functional decline. 75 Two geriatric assessment-based tools, the CARG chemotherapy toxicity calculator (shown in Appendix Table A2, online only 76 ) and the CRASH score, 76 can also be used by health care providers to understand the patient's toxicity risk and guide shared decision-making when starting a new line of treatment in an older patient. 78,79 These two calculators, which can be freely accessed online, use patient, tumor, and geriatric assessment information to predict the probability of experiencing grade $ 3 toxicities.…”
Section: Other Brief Measures and Geriatric Assessment-based Toolsmentioning
confidence: 99%
“…The proportion of patients with low grip strength was higher than that seen in the Cardiovascular Health Study (20%) 28 , and average gait speed was slower than speeds measured for community-dwelling older adults in all but one study in a large systematic review 18 . Compared with other studies of older cancer patients, our study had a larger proportion of patients with low grip strength (50% vs. 21.4%) 32 and a higher proportion with a gait speed less than 1.0 m/s (91.7% vs. 54.4%) 32 , but a smaller proportion with a prolonged time on the tug test 7,[33][34][35][36][37][38] . Because gait speed was not reported in the latter studies, it is difficult to know whether average gait speed was slower in their patients than in ours.…”
Section: Discussionmentioning
confidence: 59%
“…Some studies have reported an association between grip strength and grades 3-5 chemotherapy toxicities 32 . No association between gait speed and chemotherapy toxicity has previously been shown 32,39 , but several studies have noted an association between a tug test result exceeding 20 s and death within 6 months 34 , functional decline 38 , and early chemotherapy discontinuation 37 . The association that we observed between gait speed and chemotherapy toxicity requires confirmation in a larger study.…”
Section: Discussionmentioning
confidence: 99%